A-195 Reliability of Scores Obtained on the WAIS-IV and WISC-V in a Largely Pacific Islander Sample. (30th August 2021) - Duke, Lisa A; Ponce, Jonathan; Ahn, Jennifer; Akiyama, Kevin; Hogan, Meghan; Igarashi, Yurie; Pagat, Danielle; Petalio, Jessica; Rich, Jennifer; Stal, Lisa; Steele, Stephanie
Abstract: Objective: With the emergence of Covid-19, the field of assessment had to adapt immediately to telehealth administration without the typical rigorous standardization procedures neuropsychologists are accustomed to. This study will provide some support for reliability of scores obtained on the Wechsler Adult Intelligence Scale (WAIS-IV) and Wechsler Intelligence Scale for Children (WISC-V) utilizing telehealth in a largely Pacific Islander sample. Method: Participants were all individuals who had completed a psychological evaluation with the principal author in either a community health care clinic or a nearby independent assessment practice. Testing had to have taken place a minimum to one year prior and participant's had to be within the age range to repeat the same test that was previously administered. Thus far, there are 16 total participants. Results: Paired samples t-tests indicated that there were no significant differences between the Verbal Comprehension Index (VCI), Fluid Reasoning Index (FRI), and Working Memory Index (WMI) on the WISC-V for those administered in person and through telehealth VCI (t(4) = 2.08, p = 0.106) FRI (t(4) = −0.86, p = 0.439); and WMI (t(3) = −0.104, p = 0.924). Findings were similar for the WAIS-IV with non-significant scores on the VCI (t(5) = −0.1.3, p = 0.903) or WMI (t(5) = −0.1.3, p = 0.903). Conclusion: Although telehealth is not the gold-standard for psychological assessment, telehealth administration can provide reliable scores and important information for diagnostic clarity. As such, telehealth administration remains a valuable tool for psychologists to generate diagnoses and provide recommendations for treatment.